The fundamental principles of ancient Greek participatory democracy for contemporary Nigerian community development (2016)
Most scholarship on system of rule in ancient communities generally emphasized monarchic, aristocratic, and oligarchic forms of governments. Least accentuated is the system of participatory democracy whose provenance and prevalence has also been situated more in relative parts of contemporary Europe, America, Africa, and Asia. This gives the impression that communal participatory democracy was not very deep in the remote ancient world. The concept of participatory democracy underscores the principles of direct inclusive participation of citizens in political decisions and socio-economic policies that affect their lives in their communities, as opposed to contemporary representative participation. In classical antiquity however, the Greeks extolled the idea of communal participatory democracy by their establishment of communities (the polis, city-state), whose very existence thrived on certain fundamentals such as equality, freedom, rule of law, accountability and full citizens’ participation in communal affairs. Using the ancient city-state of Athens as a case study, this paper discusses the fundamental principles of Greek participatory democracy with a view to highlighting its implications for the development of contemporary Nigerian communities. Its main contention is that a simple revisit to the basic vital principles of Athenian democracy may positively fast-track the socio-economic and political development of many communities in contemporary Nigeria.